Negotiated rulemaking sourcebook - Pritzker, David M. (Office of the Chairman, Administrative Conference of the United States, 1995)
"The Administrative Conference published the Negotiated Rulemaking Sourcebook in 1990 as a handbook and reference manual intended primarily for use by federal agencies interested in improving their rulemaking procedures. Since that time, interest in negotiated rulemaking (or 'reg-neg') has grown substantially. With bipartisan support Congress subsequently passed the Negotiated Rulemaking Act of 1990, which was signed into law by President Bush. The Clinton Administration and the National Performance Review have also been strong supporters of this innovative procedure, which is designed to increase and improve public participation in federal agency programs. Meanwhile, Congress on several occasions has required specific use of reg-neg. Thus the need for education, advice and assistance in the effective and appropriate use of the process continues to grow. With the encouragement and financial support of the Environmental Protection Agency, the Administrative Conference has now prepared an updated version of the Sourcebook"--Chairman's foreword, page xiii.